The white nipple sign - Kasturi, Rangarajan (Frontline Gastroenterol, 2012)
The white nipple sign is a term used to describe a fresh fibrin clot on a varix that has bled recently. The authors describe a case to highlight the importance of prompt endo-therapy when this sign is recognised as disturbing this clot can cause brisk bleeding